Adjustments of Ventilator Parameters during Operating Room–to–ICU Transition and 28-Day Mortality - von Wedel, Dario; Redaelli, Simone; Suleiman, Aiman; Wachtendorf, Luca J.; Fosset, Maxime; Santer, Peter; Shay, Denys; Munoz-Acuna, Ricardo; Chen, Guanqing; Talmor, Daniel; Jung, Boris; Baedorf-Kassis, Elias N.; et al. (American journal of respiratory and critical care medicine, 2024)
Lung-protective mechanical ventilation strategies have been proven beneficial in the operating room (OR) and the intensive care unit (ICU). However, differential practices in ventilator management persist, often resulting in adjustments of ventilator parameters when transitioning patients from the OR to the ICU. To characterize patterns of ventilator adjustments during the transition of mechanically ventilated surgical patients from the OR to the ICU and assess their impact on 28-day mortality. Hospital registry study including patients undergoing general anesthesia with continued, controlled mechanical ventilation in the ICU between 2008 and 2022. Ventilator parameters were assessed one hour before and six hours after transition. Of 2,103 patients, 212 (10.1%) died within 28 days. Upon OR to ICU transition, tidal volumes and driving pressures decreased (-1.1 ml/kg predicted body weight [interquartile range -2.0 to -0.2], p<0.001 and -4.3 cmH2O [-8.2 to -1.2], p<0.001). Concomitantly, respiratory rates increased (+5.0 bpm [2.0 to 7.5], p<0.001), overall resulting in slightly higher mechanical power in the ICU (+0.7 J/min [-1.9 to 3.0], p<0.001). In adjusted analysis, increases in mechanical power were associated with higher 28-day mortality (adjusted odds ratio 1.10, 95% confidence interval [CI] 1.06 to 1.14, p<0.001, adjusted risk difference 0.7%, 95%CI 0.4 to 1.0, both per 1 J/min). During transition of mechanically ventilated patients from the OR to ICU, ventilator adjustments resulting in higher mechanical power were associated with greater risk of 28-day mortality.